MEMAHAMI KATA-KATA SUMPAH DALAM TERJEMAHAN INDONESIA SURAH AS-SYAMS DENGAN PENDEKATAN HERMENEUTIKA DOUBLE MOVEMENT FAZLUR RAHMAN - Saputra, Septian Bimo; Ramdani, Paisal; Ramdani, Sandy Muhammad; Rusmana, Dadan (IAIN Palangka Raya, 2022)
This article was initiated with the purpose of knowing and understanding the swear words in the Indonesian translation of Surah As-Syams. Because, the Qur'an is a holy book from Allah SWT. So we must understand it. But over time there are various understandings of the words contained in the Qur'an, especially the swear words in Surah As-Syams. The author here uses the hermeneutic theory of Fazlur Rahman. The methodology used is a qualitative method. The swear words is a description of the seriousness of something that is said. So, it is crucial to know and understand the meaning of the swear words. There are several swear words found in Surah As-Syams which will be the object of discussion in this article.